A Clot Twist: Extreme Variation in Coagulotoxicity Mechanisms in Mexican Neotropical Rattlesnake Venoms - Seneci, Lorenzo; Zdenek, Christina N.; Chowdhury, Abhinandan; Rodrigues, Caroline F. B.; Neri-Castro, Edgar; Bénard-Valle, Melisa; Alagón, Alejandro; Fry, Bryan G. (Frontiers in Immunology, 2021)
Rattlesnakes are a diverse clade of pit vipers (snake family Viperidae, subfamily Crotalinae) that consist of numerous medically significant species. In this paper, we used validated in vitro assays measuring venom-induced clotting time and clot strength on human plasma and fibrinogen to assess the coagulotoxic activity of three medically relevant Mexican rattlesnakes. We report the first evidence of true procoagulant activity by Neotropical rattlesnake venom in Crotalus culminatus. C. culminatus was shown to be ontogenetically-variable, with neonates being strongly procoagulant via Factor X activation, while adults were pseudo-procoagulant in that they converted fibrinogen into weak, unstable fibrin clots that rapidly broke down, thereby contributing to net anticoagulation through fibrinogen depletion. We also assessed the neutralisation of these venoms by available antivenom and also enzyme-inhibitors in order to provide crucial data for the design of evidence-based treatment strategies for envenomated patients. One of the most used Mexican antivenoms (Bioclon Antivipmyn®) failed to neutralise the potent procoagulant toxic action of neonate C. culminatus venom, highlighting limitations in snakebite management for this species. However, the metalloprotease inhibitor prinomastat substantially thwarted the procoagulant venom activity, while DMPS was much less effective. These results confirm that the Factor X activation procoagulopathy is driven by metalloproteases, while also suggesting prinomastat as a more effective management technique than DMPS. Conversely, neither metalloprotease inhibitor impeded the pseudo-procoagulant direct fibrinogen cleaving action whereas the serine protease inhibitor AEBSF did, thus revealing that the pseudo-procoagulant action is driven by kallikrein-type serine proteases. The other species studied (C. mictlantecuhtli and C. tzabcan) did not display such an ontogenetic dichotomy. Thus, this differentially ontogenetically-variable clotting factor-activating pattern poses intriguing questions concerning the possible diversity of rattlesnake venom phenotypes, an underexplored area of research. Ultimately, our findings emphasize that activity, rather than composition, is the primary target of selection pressure in venom evolution. Our results underscore the need for further research into Mexican rattlesnake venom activity patterns in order to reconstruct the evolutionary selection pressures acting upon them. Such remarkable variability in venom activity also bears considerable clinical implications regarding rattlesnake envenoming and potential shortfalls of current antivenom treatments.